Veiksmažodiniai būdvardžiai su priesagomis -tinis (-ė) ir -tinas(-a) XVI–XVII a. raštuose - Ambrazas, Saulius (Baltistica, 2001)
VERBAL ADJECTIVES WITH THE SUFFIXES -tinis (-ė) AND -tinas (-a) IN OLD LITHUANIAN TEXTS OF THE 16th–17th CENTURIES The usage of verbal adjectives with the suffixes -tinis (-ė) and -tinas (-a) in Old Lithuanian texts differs noticeably. Verbal adjectives in -tinis (-ė) (as well as in -inis, -ė) are widespread in the dictionaries by K. Sirvydas (60), based on the East High Lithuanian dialect. The greatest part of such derivatives are very rare, cf. apimtimis [apimtinis] (zwyćięski) SD3 557, apmełotinis (potwarzliwy) SD3 337 a. o. On the other hand, only one verbal adjective in -tinis (-ė) išrinktinis ‘selected choise’ has been attested in the Old Lithuanian texts of the 16th-17th centuries in the Duchy of Prussia, based on the West High and Low Lithuanian dialects. Verbal adjectives in -tinas (-a), on the contrary, are much more characteristic of the dictionary of Clavis Germanico-Lithvana (28), prepared in the Duchy of Prussia in the 17th century, than of the dictionaries by K. Sirvydas (5). At first the meaning of derivatives in -tinis (-ė) (< -tas + -inis) and-tinas (-a) (< -tas + -inas) was quite the same (cf. abejotinas ‘doubtful’ and abeiotinis (wątpliwy) SD3 471) but later the adjectives in -tinas (-a) have acquired a more specific meaning of necessity. The differences in the usage of the suffixes -tinas (-a), -tinis (-ė) and also -inas (-a), -inis (-ė) in Old Lithuanian texts have old roots. The adjectives with the old suffix *-ino- must have remained prevalent in the West Baltic dialects. On the other hand, the east part of the Baltic area is assumed to be the center of the spread of the new suffix *-ini̯o-.